2011
DOI: 10.1002/jwmg.175
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of surface‐active terrestrial salamanders in experimentally harvested forest

Abstract: Environmental temperatures affect nearly all aspects of ectotherm physiology, including terrestrial salamanders. Therefore, habitat disturbances that alter temperature regimes may interact with physiological processes to affect energy budgets of salamanders or constrain surface activity and possibly lead to changes in population-level parameters. We hypothesized that warmer surface temperatures following harvesting of canopy trees could cause surface-active salamanders to expend more energy for metabolism, pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 65 publications
2
43
0
Order By: Relevance
“…Because CWD serves as refuge to amphibians and can quickly ameliorate forest floor temperature increases in clearcuts (Homyack et al, 2011), it has been suggested as an important mitigating resource in harvested forests (deMaynadier and Hunter, 1995). We expected clearcuts with retained CWD to have greater salamander survival than those without it.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because CWD serves as refuge to amphibians and can quickly ameliorate forest floor temperature increases in clearcuts (Homyack et al, 2011), it has been suggested as an important mitigating resource in harvested forests (deMaynadier and Hunter, 1995). We expected clearcuts with retained CWD to have greater salamander survival than those without it.…”
Section: Discussionmentioning
confidence: 95%
“…Because partial harvesting does not increase temperatures or reduce canopy to the degree that clearcutting does (Todd and Andrews, 2008), it has been proposed to be a more benign practice to minimize negative impacts to amphibians (deMaynadier and Hunter, 1995). Although temperatures may still rise as much as 2-5°C in partially harvested stands relative to unharvested forests, some canopy structure and shade is retained and leaf litter is not completely removed (Todd and Andrews, 2008;Homyack et al, 2011). Similarly, retaining $50% canopy cover can result in winter low temperatures similar to those in unharvested forests (Boggs and McNulty, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism behind this pattern is unclear and warrants future research. Two intriguing hypotheses are that leaving habitat unbuffered decreases prey abundance and that increases in temperature at unbuffered sites raise the energetic cost of maintaining homeostasis [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Such interrelationships have been repeatedly demonstrated for amphibians (e.g., Welsh 1990, Karraker and Welsh 2006, Semlitsch et al 2009), many of whom are inextricably linked to mild, stable temperatures and high ambient moisture by their physiological limits (Wieser 1991, Feder andBurggren 1992). The essential role of moisture in the physiology and ecology of plethodontid salamanders is particularly well established (Spotila 1972, Feder 1983, Grover 2000, Homyack et al 2011, and is likely the v www.esajournals.org result of their late Jurassic evolution into a primarily terrestrial clade (Vieites et al 2007); with most members entirely lacking aquatic life stages (Wake and Hanken 1996). Body condition has proven highly informative for examining the relative status of amphibian populations in forested habitats (e.g., Todd and Rothermel 2006).…”
Section: Discussionmentioning
confidence: 99%